2020
DOI: 10.1055/s-0040-1712465
|View full text |Cite
|
Sign up to set email alerts
|

Professionalism of Information Management in Health Care: Development and Validation of the Construct and Its Measurement

Abstract: Abstract Background Against the background of a steadily increasing degree of digitalization in health care, a professional information management (IM) is required to successfully plan, implement, and evaluate information technology (IT). At its core, IM has to ensure a high quality of health data and health information systems to support patient care. Objectives The goal of the present study was to define what constitutes professional IM as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The last article by Thye et al described the development of an instrument to measure the professionalism of HIM professionals [ 17 ]. The researchers found that HIM professional activities comprised strategic, tactical, and operational information management.…”
Section: Resultsmentioning
confidence: 99%
“…The last article by Thye et al described the development of an instrument to measure the professionalism of HIM professionals [ 17 ]. The researchers found that HIM professional activities comprised strategic, tactical, and operational information management.…”
Section: Resultsmentioning
confidence: 99%
“…• HIT information management encompasses the full spectrum of strategic, tactical, and operational management tasks to build and operate an organization's information system [34,36]. Management practices are deemed to be essential preconditions for realizing the potential of HIT [37], especially those executed by the information technology (IT) department [38,39] and those that involve systematic clinical user participation [40,41].…”
Section: Hit Quality and Innovation Capabilitiesmentioning
confidence: 99%
“…HIT information management was operationalized using 2 constructs. First, we applied a construct that captures the degree of professionalism of information management (PIM) in health care in terms of the regularity of 15 management key tasks and practices, as proposed by Thye et al [36]. As PIM consists of 3 latent and correlated subcomponents (strategic, tactical, and operational information management), we incorporated it as a reflective higher order model with PIM as the higher order construct and the 3 subcomponents as the lower order constructs using the repeated indicator approach [68].…”
Section: Hit Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…To contribute to this knowledge gap, this article studies KM capabilities and competences and elaborates this critical aspect of KM with an aim to better understand what competences are needed to support organizational performance and renewal. In this article we complement the organizational focused view of KM with health informatics (HI) literature, which offers various frameworks for mapping HI competences (e.g., Jidkov et al, 2019;Thye et al, 2020). The article answers to the following research questions: 1) what is meant by KM competences and skills, and 2) what are the competence needs related to KM in management of health and social care?…”
Section: Introductionmentioning
confidence: 99%